Analisis Implementasi Sistem Akuntansi Piutang pada Koperasi Mekar Jaya Indonesia - Nurain Dalanggo; Rio Monoarfa; Ronal S. Badu (Al-Buhuts, 2024)
This study aims to analyze the application of the accounts receivable accounting system in the Mekar Jaya Indonesia cooperative in Gorontalo. Data analysis uses a qualitative descriptive approach with primary and secondary data sources. Data collection methods include observation, interviews, documentation, and triangulation. The results showed that the Mekar Jaya Indonesia Cooperative has implemented an accounting system, this can be seen from the information needed by management in determining the accounts receivable accounting system including related functions, accounting records used in relation to the accounts receivable accounting system and internal control elements routinely calculate the number of customer loans carried out by the Treasurer so that the accounts receivable accounting system is good enough. The receivables accounting system procedure also includes procedures for receiving and submitting loans.